Senegal : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2019)
Senegal is the first country in sub-Saharan Africa with a Francophone approach to public financial management to volunteer for a fiscal transparency evaluation (FTE). This evaluation applies the standards and practices established in the IMF's Fiscal Transparency Code (the Code), adopted in 2014. The Code is built around three pillars: (I) Fiscal Reporting; (II) Fiscal Forecasting and Budgeting; and (III) Fiscal Risk Analysis and Management. Altogether it assesses compliance with 36 FTE principles. Pillar I requires that fiscal reporting provide a thorough, relevant, current and reliable picture of general government fiscal outcomes. Pillar II requires budgets, and the macroeconomic forecasts they rely on, to spell out the fiscal objectives and policies targeted by the government; and that they provide comprehensive and credible projections of fiscal trends. Pillar III addresses the need to communicate, analyze and manage fiscal vulnerabilities and to ensure effective coordination of the public sector decision-making process. To take countries' varying degrees of institutional capacity into account, the Code differentiates between basic, good, and advanced practices for each principle. If the basic level is not attained, the practice is regarded as 'not met.'.